Samoregulacijske kompetence za nadomeščanje primanjkljajev pri učenju geografije v osnovni šoli - Knez, Sara (Revija za geografijo, 2015)
The article is based on the thesis entitled Self-regulated Learning of geography in elementary school (Knez 2015) where we examined the situation in the field of self-regulation competencies among 200 primary school pupils attending grades 6-9. Self-regulated learning can improve the weaker points in geography. However, pupils need to have certain self-regulation competences to do so. The research pointed to the incompetence of pupils in many self-regulation areas - the perception of learning geography, self-assessment, seeking help with competent persons, control over learning and using strategies for learning geography.
Keywords: geografija; geography; knowledge; learning; osnovne šole; pouk; učenje; vrednotenje; znanje